Functional Target Mapping in Plasmodium vivax P22290 for Vaccine Development using PEST- FIND Bioinformatics Tool - Dutt Jasuja , Shabir Shabina, Arvind Singh, Gaurav Sharma, Asha Sharma, Nakuleshwar (International Journal of Advanced Science and Technology, 2019)
The most prominent protein used in an invasion into the surface of the erythrocytes is called Duffy binding protein. The family in which Duffy binding protein (DBP) is included resembles Duffy binding-like erythrocyte binding proteins which are situated on the surface of the micronemes. Plasmodium vivax is a very common available causative agent of malaria disease in this world. These  protein can be very helpful for vaccine development. DARC (Duffy binding chemokine receptors) are functional motifs in P.vivax to insert in erythrocytes.These have high content of α-helical secondary structure of protein - typical of chemokine receptors.This study of PEST FIND of P22290 describes a bioinformatics approach that is used to mark specific antigen of P.vivax which has a great role in attachment of P22290 with erythrocytes. potentially involved in erythrocytes invasion. There are different protein training sets that are highly motif were built and these are tuned in specific structure based on different atmospherics and biological parameters, which are used for experimental evidence of secretion or involvement of high motif in invasion-related processes. A profile-based amino acid sequence of P22290 is used as a methodological process in the bioinformatics tool called as  PEST FIND bioinformatics tool. This tool is used to search specific proteins that can be used for targeting erythrocytes. The result of these bioinformatics tools gives us specific protein which has an essential role in the attachment of P.vivax with erythrocytes